Optimum DOA algorithms for narrowband and wideband applications - Bao, Haoji (2008)
This project targets two critical issues: to study existing algorithms and to optimize them by mitigation/elimination of performance degradation caused by phase uncertainties; to extend narrowband DOA algorithm to wideband application and provide wideband solutions.